INSTALLATION AND METHOD OF CHARACTERISTICS DEFINISION OF FRICTION AND DETERIORATION - Кіндрачук, М.; Кульговий, Е.; Данілов, А.; Хлевна, Ю. (Science-based technologies, 2010)
The method of definition of characteristics of deterioration in the form of statistical models is considered. Application of the statistical analysis is connected with internal structure of process of deterioration, the example of constructions of the characteristic in the form of a polynom of the second degree is resulted. The following test setup, its characteristics, and circuit testing.